Is There A Doctor Onboard? - Holly Cathryne Brownlee (University Library System, University of Pittsburgh, 2021)
I never expected to be asked the question 'can you confirm to the pilot we need to divert the plane' while in my final year of medical school yet this was the question posed to me during a recent experience somewhere over mainland Europe.